The Saint - Brown, David; Evans, Roberts; Macdonald, William J.; Neufeld, Mace; Noyce, Philip; Kilmer, Val 1959-; Shue, Elisabeth 1963-; Serbedzija, Rade 1946-; Paramount Pictures (Hollywood, California Paramount, 1997)
An array of sophisticated gadgetry is at Templar's commnad as he plunges into a cloak-and-dagger netherworld of move and countermove. Cool, too, is Templar's knack for coming up with the right disguise at the right time.
Costume designer, Marlene Stewart ; Music composed by Graeme Revell ; Edited by Terry Rawlings ; Production designer, Joseph Nemec III ; Director of photography, Phil Meheix ; Executive producers, Paul Hitchcock and Robert S. Baker ; Screenplay by Jonathan Hensleigh and Wesley Strick.
Val Kilmer, Elisabeth Shue, Rade Serbedzija.
VHS format.
In Enlish.
Keywords: Suspense in motion pictures; Adventure films